Karakteristik Mortar Polimer Epoxy Resin Dengan Fiberglass - Bambang Utomo; Siti Aisyah Nurjannah; Saloma (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
Nowadays, the developments of technology in construction are progressing very rapidly, one of which is mortar without using cement material. This encourages the development of concrete and mortar technology so that it can be widely used to repair structural or non-structural damages. In these conditions, a binder is needed in the form of an epoxy resin polymer with added fiberglass to get a strong material result in a short time. A mixture of 75% sand and 25% epoxy resin from the volume of the test object resulted a mortar compressive strength of 35.50 MPa with a specific gravity of 1.505 kg/m3. The results showed that the variation of the compressive strength of the epoxy resin mortar without fiber was higher than the variation with fiberglass. This was due to the addition of fiberglass reducing the composition of the percentage of epoxy resin which results in reduced bonding power in the mixture. The flexural strength of a mortar with variations using fiberglass was 8 MPa and showed the best performance, although the difference was not too far from the variation without fiberglass. This was because the addition of fiberglass can reduce cracks, so that the fibers can bind well. The tests had been carried out including tests of the compressive strength, flexural strength, and Scanning Electron Microscope (SEM).